Eco-Biology of the Orbiculate Cardinalfish, Sphaeramia orbicularis in Seagrass Habitats of Pari Island, Indonesia - Khasanah, Siti; Simanjuntak, Charles Parningotan Haratua; Yulianto, Gatot (Universitas Gadjah Mada, 2025)
The seagrass ecosystem of Pari Island, Kepulauan Seribu National Park, provides essential habitat for various fish resources, such as Sphaeramia orbicularis. Little information has been reported on the biology and ecology of this species in Indonesia. This study describes the growth pattern, feeding ecology, and reproductive biology of S. orbicularis in the seagrass beds of Pari Island. Fish samples were collected monthly from November 2023 to April 2024 using a beach seine net. A total of 542 fish were obtained with a range of 17-85 mm and weights of 0.16-24.28 g. Fish growth patterns were isometric and positive allometric with condition factor values >1. Based on feeding ecology, S. orbicularis is categorized as a specialist and has a low niche breadth (BA=0.2), with the primary diet being Gammaridae, Tanaidacea, and Brachyura. The fish population has a balanced sex ratio and spawns in January. This is indicated by the highest GMS mature gonad and GSI values found in that month. Egg fecundity ranged from 7,239-12,240 eggs with an average diameter of 0.0048-0.0052 mm, indicating a total spawner spawning pattern. The length of the first gonad maturity of male fish was 63.12 mm, while that of female fish was 65.27 mm.